Research Bulletin, March 2015. (IMF Research Bulletin; IMF Research Bulletin ;, 2015)
Articles in the March 2015 Research Bulletin focus on the oil market, energy subsidies, and output. The Research Summary on "An Exploration in Deep Corners of the Oil Market," authored by Rabah Arezki, Douglas Laxton, Armen Nurekyan, and Hou Wang, examines fluctuations in oil prices. "The State Budget May Afford It All," by Christian Ebeke and Constant Lonkeng Ngbouana, reviews energy subsidies and their fiscal, distributional, and environmental costs. In the 'Q and A' column Pau Rabanal takes a look at 'Seven Questions on Potential Output.' The Bulletin includes a listing of recent IMF Working Papers, Staff Discussion Notes, recommended readings from IMF Publications, and a call for papers for the next Annual Research Conference. A link with information and free access to IMF Economic Review is also included.